2016
DOI: 10.3758/s13423-016-1142-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating valence from the sound of a word: Computational, experimental, and cross-linguistic evidence

Abstract: It is assumed linguistic symbols must be grounded in perceptual information to attain meaning, because the sound of a word in a language has an arbitrary relation with its referent. This paper demonstrates that a strong arbitrariness claim should be reconsidered. In a computational study, we showed that one phonological feature (nasals in the beginning of a word) predicted negative valence in three European languages (English, Dutch, and German) and positive valence in Chinese. In three experiments, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 13 publications
2
34
0
2
Order By: Relevance
“…It is rather uncontroversial that human language is a symbolic system in the sense that, generally speaking, word form is arbitrarily associated to meaning in the external or psychological world, for example, there is nothing in the sound of the words “table” or “love” that links to the four-legs object on which we can put things or that special affection that we feel for our closest (e.g., Hockett, 1963; Saussure, 1916). Nevertheless, actual lexicons (and linguistic experience more in general; e.g., Louwerse & Connell, 2011; Monaghan et al, 2011) are full of non-arbitrary associations between form and meaning (e.g., Louwerse & Qu, 2017), possibly as the result of learning constraints in the cultural evolution of languages, which may have introduced some systematicity in an in-principle random domain (e.g., Kirby et al, 2008). Whether our cognitive system captures these associations and uses them to inform language processing is an unsettled issue, and a potentially revealing one in terms of the cognitive machinery that supports human language.…”
Section: Introduction: the Relevance Of Form–meaning Mapping For Wordmentioning
confidence: 99%
“…It is rather uncontroversial that human language is a symbolic system in the sense that, generally speaking, word form is arbitrarily associated to meaning in the external or psychological world, for example, there is nothing in the sound of the words “table” or “love” that links to the four-legs object on which we can put things or that special affection that we feel for our closest (e.g., Hockett, 1963; Saussure, 1916). Nevertheless, actual lexicons (and linguistic experience more in general; e.g., Louwerse & Connell, 2011; Monaghan et al, 2011) are full of non-arbitrary associations between form and meaning (e.g., Louwerse & Qu, 2017), possibly as the result of learning constraints in the cultural evolution of languages, which may have introduced some systematicity in an in-principle random domain (e.g., Kirby et al, 2008). Whether our cognitive system captures these associations and uses them to inform language processing is an unsettled issue, and a potentially revealing one in terms of the cognitive machinery that supports human language.…”
Section: Introduction: the Relevance Of Form–meaning Mapping For Wordmentioning
confidence: 99%
“…The evidence for nonarbitrary sound-to-meaning correspondences also extends to statistical regularities for abstract versus concrete words (Reilly, Westbury, Kean, & Peele, 2012) and words with positive or negative valence across languages (Adelman, Estes, & Cossu, 2018;Tillman & Louwerse, 2018;Louwerse & Qu, 2017). Although researchers have often described action words as being grammatically ambiguous when presented in isolation, that is, they may be understood as either verbs or nouns (e.g., Pulvermüller, Hauk, Nikulin, & Ilmoniemi, 2005), there is a substantial body of psycholinguistic research demonstrating the degree to which a word's orthography and/or phonology is typical of other words in its grammatical category influences on-line processing, particularly for verbs and nouns.…”
Section: Introductionmentioning
confidence: 72%
“…In addition to action semantics, these perspectives typically emphasize roles for brain regions in processing meaning based on data from comparisons of abstract versus concrete words and words with positive or negative valence. Yet, statistical regularities in sound-to-meaning correspondences also distinguish these classes of words across languages (Adelman et al, 2018;Tillman & Louwerse, 2018;Louwerse & Qu, 2017;Reilly et al, 2012). Accounts that explicitly assume an arbitrary relationship therefore need amending (e.g., Glenberg & Kaschak, 2002), whereas those that omit roles for systematic sound-to-meaning correspondences might be considered underspecified at best (e.g., Lambon Ralph et al, 2017;Meteyard et al, 2012;Barsalou, 2008;Pulvermüller, 2005;Zwaan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the driving question that motivated this study was whether a specific sound–meaning relation that has repeatedly been observed in studies from various academic disciplines can also be found in poetry. At the same time, results from recent studies suggest that there are also other features that proved to be statistically significant predictors for phonosemantic relations, such as articulatory characteristics of phonemes or the frequency of occurrence of individual phonemes (e.g., Louwerse & Qu, 2017; Nastase et al, 2007; Ohtake & Haryu, 2013). In fact, Monaghan and Fletcher (2019) reported that the frequency of individual phonemes outperforms phonetic features as a predictor for sound–meaning relations of nonwords.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas these three studies employed questionnaires to directly test sound-iconic associations with vowels' articulatory-acoustic features, recent studies applied more indirect approaches. For example, some studies considered the relative occurrence of phonemes or phonetic-acoustic features in annotated wordlists (i.e., wordlists with ratings for Valence and Arousal per word) as an indicator for the emotional connotations of these phonemes (e.g., Adelman, Estes, & Cossu, 2018;Aryani, Conrad, et al, 2018;Louwerse & Qu, 2017). Similar strategies to tackle associations between phonemes (or phonetic features) and emotional tone have previously been applied by Ertel (1965) and Heise (1966).…”
Section: Research Objective and Hypothesismentioning
confidence: 99%